Survey on comultiplication modules - Habibollah Ansari-Toroghy; Faranak Farshadifar (Surveys in Mathematics and its Applications, 2019)
The concept of comultiplication (as a dual notion of multiplication) modules was introduced and studied by H. Ansari-Toroghy and F. Farshadifar in 2007. This notion has obtained a great attention by many authors and now there is a considerable amount of research concerning this class of modules. The main purpose of this paper is to collect these results and provide a useful source for those who are interested in research in this field.